Grandpa Monty's muddles - Zafrilla, Marta, 1982- (Cuento de Luz, 2012)
Grandpa Monty gets things a bit muddled these days--he put a chicken in the washing machine, roasted a sweater, and ironed a piece of fish! When he moves in with his son's family, 7-year-old grandson Oscar tries to help Grandpa Monty remember things, not always with the best results. A gentle and humorous look at dealing with dementia in the family.